2018
DOI: 10.3390/mca23020018
|View full text |Cite
|
Sign up to set email alerts
|

A Family of 5-Point Nonlinear Ternary Interpolating Subdivision Schemes with C2 Smoothness

Abstract: Abstract:The occurrence of the Gibbs phenomenon near irregular initial data points is a widely known fact in curve generation by interpolating subdivision schemes. In this article, we propose a family of 5-point nonlinear ternary interpolating subdivision schemes. We provide the convergence analysis and prove that this family of subdivision schemes is C 2 continuous. Numerical results are presented to show that nonlinear schemes reduce the Gibbs phenomenon significantly while keeping the same order of smoothne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In this article, we proposed a general formula for (2n−1)-point nonlinear ternary interpolating subdivision schemes. It is shown that 3-point and 5-point nonlinear ternary subdivision schemes developed in ( [4], [5]) are special cases to our proposed schemes. Convergence of another special case (5-point nonlinear ternary interpolating subdivision scheme) is proved and it is shown that it is at least C 2 continuous.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In this article, we proposed a general formula for (2n−1)-point nonlinear ternary interpolating subdivision schemes. It is shown that 3-point and 5-point nonlinear ternary subdivision schemes developed in ( [4], [5]) are special cases to our proposed schemes. Convergence of another special case (5-point nonlinear ternary interpolating subdivision scheme) is proved and it is shown that it is at least C 2 continuous.…”
Section: Resultsmentioning
confidence: 98%
“…The above equation can be simplified to the the following subdivision scheme of [5] which is C 2 for 1 324 < w < 1 162 .…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…The nonlinear subdivision schemes that have been applied in practical situations until now (see for example [1,2,3,4,5,9,10]) are usually compatible with either the point-value framework or the cell-average framework. Since our interest for the present work lays outside of these frameworks, we will focus only on the linear case.…”
Section: Introductionmentioning
confidence: 99%